STUDENT PERCEPTION OF UPN "VETERAN" YOGYAKARTA BRAND IMAGE AS A NEW STATE UNIVERSITY - Swastika Ajeng Dewanti; Siti Fatonah; Subhan Afifi (The Indonesian Journal of Communication Studies, 2018)
This study aims to identify how the perception of UPN "Veteran" Yogyakarta students about the brand image owned by UPN "Veteran" Yogyakarta, to know what are the obstacles and developments that happened after UPN "Veteran" Yogyakarta became the country. Type of research used in this research is descriptive research type with qualitative method. The theory used is the theory of perception and brand image. Data collection techniques in this study were obtained through interviews, direct observation and documentation. The results showed that the brand image owned UPN "Veteran" Yogyakarta post to State College of New State is a state defense that should be realized not only in the country but also on the international scene. Student perception on brand image UPN "Veteran" Yogyakarta in its application is good enough, because it has applied discipline to the students, lecturers, and employees of UPN "Veteran" Yogyakarta, and the state defend has been attached not only to the students but also to the wider community. However, in the implementation and understanding of the state defense has not been maximal, so there are still UPN "Veteran" Yogyakarta students who do not know how the brand image owned UPN "Veteran" Yogyakarta.